We need doctors - Schaefer, Lola M. (Mankato, Minnesota : Capstone Press, 2000)
Simple text and photographs present doctors and their role in the community.
Includes bibliographical references and index.
Keywords: Physicians -- Juvenile literature; Medicine -- Juvenile literature